Marketing político en twitter :caso Mauricio Rodas - Pacheco Toro, Edwin Francisco (2016)
This paper reviews the case of the political campaign in the candidacy of Mauricio Rodas in social networks (RRSS), its impact on the political level and also tries to make an approach to how social networks are in a communication strategy of the campaigns. The RRSS have become generators of opinion, achieving a direct interaction with the candidate through the candidate's account. This analysis is done we will see a strategy within which arise early communicative action are those social contexts in which the goal is mutual understanding. Thus communication strategies and armor are generated for the candidate not worry about misinformation and is dedicated to the main thing campaigning. All posts are linked to a policy depending on the needs and strategy are linked to a communications strategy to provide a context for each message and not remain as something loose that generates distrust of the elector. All these communicative actions are designed to attract followers to help create communities of support for the bid and thus generate a shield to the politician without having to get out in front of every argument and thus free the candidate to be completely dedicated to transmit messages proactive to attract undecided voters and build trust when giving their vote in the ballot box.